Factors Affecting the Development of Sports Activity from the Sports Teams’ Points of View (International Journal of Psychosocial Rehabilitation, 2020)
The study aims to identify the factors of the development of sports activity from the point of view of students from the sports teams. It attempts to determine the role of the type of sport, gender and level of study in determining these factors. To achieve this, the study was conducted on a random sample of 57 students, who are at different stages of their education, from the various sports teams in a university, including both individual and team sports. A questionnaire was applied consisting of four aspects: communication, financial resources, advertisement and incentives. The study results revealed that the development of the sports activity in the university from the athletic teams’ views was particularly high. Additionally, the aspect of financial resources had the greatest role in the evolution of sports activity followed by the communication aspect. Furthermore, the study results conveyed that the gender, type of sport, and level of education had no effect on the advancement in sports at the university. It is recommended to direct the efforts of the university administration to raise the level of participation of students in sports activities because of its importance in the growth and refinement of their personality.